COMMUNITY DEVELOPMENT THROUGH SOCIAL ACTION: A STUDY OF THE IMPACT OF COMMUNITY-LED INITIATIVES ON SOCIAL CHANGE IN SOUTH AFRICA - Phoke Alpa Rakgwata; Janine Shout Ramothwa; Decent Munzhelele (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Community development through social action has emerged as a crucial pathway for addressing socio-economic challenges and promoting sustainable change. The study explores the role of community-led initiatives in fostering social change within South Africa, focusing on how such grassroots movements contribute to the broader process of community development. The aim of the study is to investigate the impact of community-driven actions on social change, examining their effectiveness in addressing local issues, empowering marginalized groups, and promoting sustainable development. A qualitative approach was employed to capture the depth and nuances of community experiences, with exploratory research guiding the investigation into various community-led programs and their outcomes. Comprehensive desktop research was utilized to gather secondary data, drawing on existing literature, reports, and case studies relevant to the topic. The data collected was then analyzed using thematic analysis to identify key patterns and themes that shed light on the ways in which community action influences social transformation. The findings contribute to a deeper understanding of the transformative potential of community-led initiatives and offer insights for policy makers, practitioners, and scholars seeking to enhance social development in South Africa and similar contexts.